SOCIAL CLASSES IN THE CANTERBURY TALES - Eldorbek Erkin og’li Khamitov; Turabayeva Ruhshona O’ktambekovna (TADQIQOTLAR, 2026)
Abstract This study investigates the representation of social classes in Geoffrey Chaucer’s The Canterbury Tales, focusing on how the work mirrors the hierarchical structure of late medieval English society. Chaucer introduces a diverse cast of characters from various social backgrounds, including nobility, clergy, merchants, artisans, and peasants, offering a detailed and multifaceted depiction of the social order. Each character’s story and behavior reflect their social rank, illustrating the values, ambitions, and challenges unique to their class. The analysis explores how Chaucer employs humor, irony, and satire to critique social conventions, reveal hypocrisy, and expose the tensions existing among different social groups. Through the interactions of characters during the pilgrimage, the text reveals both the rigid structure and the potential for social mobility in medieval England. Additionally, the tales shed light on contemporary perspectives regarding wealth, education, gender roles, and morality, providing insight into the everyday experiences and beliefs of people across social strata. Ultimately, The Canterbury Tales is not only a literary achievement but also a valuable historical source that illuminates the intricacies of medieval social hierarchies. Chaucer’s work continues to impact modern literary studies and social thought, underlining the importance of understanding class relations through literature.